Interactive role of endocrine stress systems and reproductive hormones in the effects of stress on declarative memory. (October 2020) - Cohen, Ami; Zemel, Chen; Colodner, Raul; Abu-Shkara, Randa; Masalha, Refaat; Mahagna, Lila; Barel, Efrat
Highlights: Stress disrupts recall after interference on a declarative memory task. Effects of stress on memory are associated with sex hormones-stress systems interaction. Effects of stress on memory appear to be modulated by baseline levels of sex hormones. Abstract: The effects of stress on memory performance, and the neuroendocrine mechanisms mediating such effects, are not well understood. Given the interrelationship between reproductive hormones and both the sympathetic nervous system (SNS) and the hypothalamic-pituitary-adrenal axis (HPA-A), we examined their combined effect on stress-induced modulation of declarative memory. Before and after exposure either to the Trier Social Stress Test (TSST) procedure or to a non-stress condition, 112 participants completed the Rey Auditory Verbal Learning Test. We analyzed participants' HPA-A and SNS reactivity by measuring cortisol and salivary alpha-amylase (sAA, an SNS activation marker) in four saliva samples. In addition, testosterone, estradiol, and progesterone were sampled prior to the stress exposure. Exposure to the TSST attenuated memory recall after an introduction of an interference list during the declarative memory task. Importantly, controlling for testosterone, estradiol, and progesterone diminished this effect of stress, suggesting the importance of baseline reproductive hormones in stress-induced modulation of memory functions. Furthermore, a multiple regression model revealed that stress-induced declines in memory performance were negatively associated with participants' stress-induced cortisol reactivity, but only among individuals with high testosterone levels. In addition, stress-induced declines in memory performance were negatively associated with participants' stress-induced increases in sAA, but only in individuals with low progesterone levels. These findings suggest that the effects of stress on memory performance may be modulated by baseline reproductive hormones and provide a preliminary indication for specific modulatory interrelationships between reproductive hormones and neuroendocrine stress mechanisms in mediating the effects of stress on memory.